Implementasi Algoritma Multi Group Huffman Dalam Kompresi File Teks Dokumen - Rosanny N Sihombing (Buletin Ilmiah Informatika Teknologi, 2023)
Technological advances for Data and imformation compression have developed rapidly in the digital era and has become a very important necessity to establish a fast exchange of information. Many conveniences given, one of which is the ease in wrting document data storage in digital from. With the existing convenience, it isnot directly proportional to digital document storage media due to the rapid growth on document data which is getting bigger and bigger day by day. Meawhile in existing storage is still very limited. In the research,the method used is a multi group algorithm huffman. This method works by coding in a form bits to represent the data under study. In general data compression is distinguished in twi types, namely data compression does not change the original data and lossy data compression is data compression the result of the compression are not the same as the original data .Multi Group Method Huffman falls into the Losesless Data Compression category. Huffman is one of the compression algorithms. Huffman compression technique can provide savings in storage. Huffman works based on thefrequency of the chracters are the same, the more high level of compression obtained.